IMPLEMENTATION OF ISLAMIC VALUES WITH THE ISLAMIC PARENTING MODEL FOR FINAL STUDENTS AT THE WALI SONGO NGABAR ISLAMIC BOARDING SCHOOL, PONOROGO - Mukhlis Nur Pancahari; Moch Faiz Ansori; Nurul Iman; Wahyudi Setiawan (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
The Boarding School, an Islamic educational institution, has long helped build the character and spirituality of the center. Trainees have a very important role to play in instilling Islamic values because the santri akhir are in the final stages of learning in the training before entering society. The process of parenting at the training plays an important role in providing the moral and spiritual foundation to the last centri. The objective of this study is to find out the Islamic values embedded in the santri akhir, to analyze the implementation of Islamic Values in the santri akhir, to evaluate Islamic model of parenting in the application of the Islamist values at the santri akhir in Wali Songo Ngabar Boarding School. The type of research carried out by researchers is field research using qualitative research methods. The method in data collection uses observations, interviews and documentation. The Islamic values implanted in the santri akhir of the Wali Songo Ngabar Boarding School take inspiration from the Panca Jiwa visited by the residence, Implementation of the Islamist values in the santri akhir in the Wali Songo Ngabar Boarding School, the musyrif ensures that in every activity, the chanceller practices values, Wali Songo Ngabar Boarding School adopts a holistic and integrated Islamic model of foster care